2022
DOI: 10.3390/cells11040620
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Hepatic Autophagy by Nuclear Receptors

Abstract: Autophagy is an adaptive self-eating process involved in degradation of various cellular components such as carbohydrates, lipids, proteins, and organelles. Its activity plays an essential role in tissue homeostasis and systemic metabolism in response to diverse challenges, including nutrient depletion, pathogen invasion, and accumulations of toxic materials. Therefore, autophagy dysfunctions are intimately associated with many human diseases such as cancer, neurodegeneration, obesity, diabetes, infection, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 220 publications
(248 reference statements)
0
7
0
Order By: Relevance
“…The autophagosomes engulf the nucleus and then fuse with lysosomes, which contain hydrolytic enzymes that break down the contents of the autophagosomes [ 18 ]. Autophagy shows involvement in various cellular processes, such as the DNA damage response, cellular senescence, and cellular metabolism regulation [ 19 , 20 , 21 , 22 ]. Additionally, it implicates in the onset of several diseases, including cancer [ 23 ] and neurodegenerative disorders [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The autophagosomes engulf the nucleus and then fuse with lysosomes, which contain hydrolytic enzymes that break down the contents of the autophagosomes [ 18 ]. Autophagy shows involvement in various cellular processes, such as the DNA damage response, cellular senescence, and cellular metabolism regulation [ 19 , 20 , 21 , 22 ]. Additionally, it implicates in the onset of several diseases, including cancer [ 23 ] and neurodegenerative disorders [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PXR may be a promising target for the prevention and treatment of liver disease based on its transcriptional regulation in inflammation, liver injury, and maintenance of homeostasis. PXR has also been shown to regulate liver autophagy and apoptosis pathways, thus having hepatoprotective effects in various liver injuries ( 44 , 45 ). PXR-null mice were reported to have more severe liver damage and suppressed autophagy flow in mice ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…This regulation influences various cellular processes, including endocytosis, lysosomal function, exocytosis, autophagy, and phagocytosis. 54 Research on nanoparticle drug delivery has shown that when nanocarriers enter cells through the endocytic pathway, they are transported to lysosomes as endosomes become more acidic and mature. As a result, the drugs enclosed within the nanocarriers are vulnerable to degradation by digestive enzymes.…”
Section: Cluster Analysis Of Protein Expression Patternsmentioning
confidence: 99%